Video Pembelajaran Addie untuk Meningkatkan Keterampilan Baca Puisi Remaja Pedesaan - Rizal Ansori; Liza Murniviyanti; Darwin Effendi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study is oriented toward the development and testing of an instructional video product intended to facilitate the enhancement of expressive poetry reading competencies among adolescents at Sanggar Swarna Art, Penukal Abab Lematang Ilir Regency. A quantitative framework was employed, with the ADDIE model serving as the procedural foundation. The participants comprised 50 respondents in the needs-assessment phase, 3 individuals in one-to-one trials, 8 in small-group trials, and 20 in field testing. Data were garnered through needs-analysis questionnaires, expert-validation instruments, usability scales, and performance rubrics for poetry reading. Expert appraisals yielded a mean score of 4.37 out of 5, categorizing the product as highly viable across substantive, media, and linguistic dimensions. The field test revealed an average poetry reading skill score of 3.69 out of 5, with articulation registering the highest achievement (3.85) and eye contact the lowest (3.55). The usability index attained 90 out of 100, while user satisfaction reached 94 out of 100. Grounded in Gravemeijer et al.'s (2006) benchmarks, the product satisfies validity, practicality, and effectiveness criteria, rendering it suitable as a self-directed learning aid and supplementary resource for verbal arts training in rural settings.